Evaluation of an automatic opening window system to maintain adequate ventilation rates - Tsutsumi Akane; Lee Sihwan (E3S Web of Conferences, 2022)
Under the influence of COVID-19, it is recommended to ventilate to reduce the risk of infection in the room. In an air-conditioned room, opening windows increase the ventilation rate that caused by indoor and outdoor temperature differences. However, there is a concern that opening windows in the air-conditioned room will increase the heating and cooling loads due to air leakage. In addition, it is difficult to maintain the adequate ventilation rate. To solve this problem, we developed an automatic window opening system to control the natural ventilation rate. This system can be controlling the adequate ventilation rate for the room by adjusting the opening area of window automatically. The purpose of this study is to confirm the effectiveness of this system and to understand its performance. In this study, analysis was done to calculate the adequate opening width in Japan, and actual measurements were conducted to understand the operating performance of this system. As a result, it was confirmed that sensible heat load due to ventilation was reduced with this system, and the ventilation rate could be controlled by this system.